A Review on the Role of Irisin in Insulin Resistance and Type 2 Diabetes Mellitus - Mamo Gizaw; Pandi Anandakumar; Tolessa Debela (Korean Pharmacopuncture Institute, 2017)
Irisin is a novel hormone like polypeptide that is cleaved and secreted by an unknown protease from fibronectin type III domain-containing protein 5 (FNDC5), a membrane- spanning protein and which is highly expressed in skeletal muscle, heart, adipose tissue, and liver. Since its discovery in 2012, it has been the subject of many researches due to its potent physiological role. It is believed that understanding irisin's function may be the key to comprehend many diseases and their development. Irisin is a myokine that leads to increased energy expenditure by stimulating the 'browning' of white adipose tissue. In the first description of this hormone, increased levels of circulating irisin, which is cleaved from its precursor fibronectin type III domain-containing protein 5, were associated with improved glucose homeostasis by reducing insulin resistance. Irisin is a powerful messenger, sending the signal to determine the function of specific cells, like skeletal muscle, liver, pancreas, heart, fat and the brain. The action of irisin on different targeted tissues or organs in human being has revealed its physiological functions for promoting health or executing the regulation of variety of metabolic diseases. Numerous studies focus on the association of irisin with metabolic diseases which has gained great interest as a potential new target to combat type 2 diabetes mellitus and insulin resistance. Irisin is found to improve insulin resistance and type 2 diabetes by increasing sensitization of the insulin receptor in skeletal muscle and heart by improving hepatic glucose and lipid metabolism, promoting pancreatic β cell functions, and transforming white adipose tissue to brown adipose tissue. This review is a thoughtful attempt to summarize the current knowledge of irisin and its effective role in mediating metabolic dysfunctions in insulin resistance and type 2 diabetes mellitus.